Odpowiedzi

2009-11-21T16:00:06+01:00
2(x^2-9)-(x^2-4x+4)=
2x^2-18-x^2+4x-4=x^2+4x-22 gdzie x^2 oznacza x do potęgi drugiej

2. 5x=x+9
x+y=3

5x-x=9
x+y=3

4x=9
x+y=3

x=9/4
9/4+y=3

x=9/4
y=3-9/4

x=9/4
y=2/4
2009-11-21T16:03:20+01:00
1. [2(x-3)(x+3)(x-2)]²=[2x-6*x+3*x-2]²=[2x-6x+3x-2]²=[-x-2]²=-x²-4
2. 5x=x+9
-x=4
x=-4
2009-11-21T16:03:01+01:00
2(x-3)(x+3)-(x-2)²=2(x²-9)-(x²-4x+4)=2x²-18-x²+4x-4=x²+4x-22

5x=x+9
x+y=3

x=3-y
5(3-y)=(3-y)+9

x=3-y
15-5y=3-y+9

x=3-y
15-5y=-y+12

x=3-y
-5y+y=12-15

x=3-y
-4y=-3 /*(-1)

x=3-y
4y=3


x=3-y
y=3/4


x=3-3/4
y=3/4

x=2 1/4
y=3/4